Association between the ratio of anti-angiogenic isoform of VEGF-A to total VEGF-A and adverse clinical outcomes in patients after acute myocardial infarction. (June 2018) - Harada, Kazuhiro; Kikuchi, Ryosuke; Ishii, Hideki; Shibata, Yohei; Suzuki, Susumu; Tanaka, Akihito; Suzuki, Atsuo; Hirayama, Kenshi; Murohara, Toyoaki
Abstract: Background: Vascular endothelial growth factor-A (VEGF-A) promotes neovascularization and is attracting considerable attention as a remarkable risk factor in patients after acute myocardial infarction (AMI). In contrast, the association between VEGF-A165 b, which is the main anti-angiogenic isoform of VEGF-A, and adverse clinical outcomes after AMI remains unclear. The present study aimed to investigate the association between serum VEGF-A165 b and major adverse cardiac and cerebrovascular events (MACCEs) after percutaneous coronary intervention (PCI) for AMI. Methods: We evaluated 23 patients with AMI who underwent primary percutaneous coronary intervention. VEGF-A and VEGF-A165 b levels were measured on admission (day 1) and at days 3, 7, and 30 after PCI. Results: The levels of total VEGF-A tended to be lower, while the ratio of VEGF-A165 b to total VEGF-A tended to be higher in patients with MACCEs than in those without. The patients with a high ratio of VEGF-A165 b to total VEGF-A had a significantly higher risk of MACCEs using the cut-off values for MACCEs at day 30 after PCI (0.87 vs. 0.25, log-rank test, p = 0.0058). Conclusion: The assessment of VEGF-A165 b combined with VEGF-A may be a valuable screening tool for predicting MACCEs in clinical practice.